The Bandini quartet : Wait until spring, Bandini ; The road to Los Angeles ; Ask the dust ; Dreams from Bunker Hill /: Wait until spring, Bandini ; The road to Los Angeles ; Ask the dust ; Dreams from Bunker Hill. (2014) - Fante, John, 1909-1983
No abstract available